Estimating monthly PM2.5 concentrations from satellite remote sensing data, meteorological variables, and land use data using ensemble statistical modeling and a random forest approach. (15th December 2021) - Chen, Chu-Chih; Wang, Yin-Ru; Yeh, Hung-Yi; Lin, Tang-Huang; Huang, Chun-Sheng; Wu, Chang-Fu
Abstract: Fine particulate matter (PM2.5 ) is associated with various adverse health outcomes and poses serious concerns for public health. However, ground monitoring stations for PM2.5 measurements are mostly installed in population-dense or urban areas. Thus, satellite retrieved aerosol optical depth (AOD) data, which provide spatial and temporal surrogates of exposure, have become an important tool for PM2.5 estimates in a study area. In this study, we used AOD estimates of surface PM2.5 together with meteorological and land use variables to estimate monthly PM2.5 concentrations at a spatial resolution of 3 km 2 over Taiwan Island from 2015 to 2019. An ensemble two-stage estimation procedure was proposed, with a generalized additive model (GAM) for temporal-trend removal in the first stage and a random forest model used to assess residual spatiotemporal variations in the second stage. We obtained a model-fitting R 2 of 0.98 with a root mean square error (RMSE) of 1.40 μ g / m 3 . The leave-one-out cross-validation (LOOCV) R 2 with seasonal stratification was 0.82, and the RMSE was 3.85 μ g / m 3, whereas the R 2 and RMSE obtained by using the pure random forest approach produced R 2 and RMSE values of 0.74 and 4.60 μ g / m 3, respectively. The results indicated that the ensemble modeling approach had a higher predictive ability than the pure machine learning method and could provide reliable PM2.5 estimates over the entire island, which has complex terrain in terms of land use and topography. Graphical abstract: Image 1 Highlights: An improved two-stage ensemble modeling compared to random forest approach. Leave one out cross-validation R2 0.82 and root mean squared error 3.85  μ g/ m 3. Higher correlation between ground PM2.5 concentrations and AOD estimate of PM2.5 Long-term PM2.5 concentrations across Taiwan substantially declined from 2015 to 2019.